The effect of music media on breast cancer prevention on knowledge and satisfaction among female service recipients at Ubon Ratchathani Cancer Hospital - Prakobchit, Sairung; Tubtimhin, Sopit; Wamalun, Chaliya (UBRU Journal for Public Health Research, 2025)
This quasi-experimental study with a two-group comparison aimed to investigate the effects of breast cancer prevention music media on the knowledge and satisfaction of female service recipients at Ubon Ratchathani Cancer Hospital. The study was conducted with 56 female participants, divided into an experimental group and a control group of 28 each, randomly assigned using computer software. The research instruments included: (1) the experimental tool, breast cancer prevention music media developed from a literature review and adapted to modern music. The content was based on the World Health Organization’s breast cancer prevention guidelines, covering four aspects: healthy eating, physical exercise, stress management, and self-breast examination; and (2) the data collection tools, comprising a breast cancer knowledge assessment and a satisfaction assessment. The tools demonstrated strong quality, with content validity indices (CVI) of .95, .90, and .97, respectively. Data were analyzed using frequency, percentage, mean, standard deviation, paired t-test, and independent t-test, with a significance level set at 0.05. The results showed that the experimental group’s mean knowledge score increased significantly from 7.96 (SD = 1.89) to 11.89 (SD = 1.55), higher than both their pre-test scores and the control group’s mean score of 8.04 (SD = 0.33) (p < .001). Regarding satisfaction, the experimental group reported a significantly higher mean satisfaction score (Mean = 4.25, SD = 0.52) compared with the control group (Mean = 2.15, SD = 0.48) (p < .001). Analysis of satisfaction dimensions in the experimental group indicated that overall content and melody received the highest ratings (Mean = 4.65, SD = 0.47), followed by ease of understanding (Mean = 4.46, SD = 0.49), while comprehensiveness of breast cancer prevention content received the lowest rating (Mean = 3.84, SD = 1.02). In conclusion, the findings suggest that breast cancer prevention music media is effective in enhancing knowledge and increasing engagement among female service recipients compared with traditional document-based information. The hospital has implemented this innovation by broadcasting the music daily through its PA system and producing videos for dissemination on social media platforms such as YouTube. It is recommended that this music-based health education approach be expanded to other diseases in the future.